Penerapan Service Learning Dalam Program Kebersihan Lingkungan Di Yayasan Himatun Ayat - Ikrimah; Sirotul Hasanah; Riska Ratna Nengsih; Novi Hidayati Afsari (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2025)
Environmental cleanliness remains a critical issue in social and educational institutions, influencing not only physical health but also character development, discipline, and social awareness. This article describes the implementation of service-learning in an environmental cleanliness program at the Himatun Ayat Foundation, integrating community service with reflective learning so participants can translate knowledge into concrete action. The program was designed to address key challenges identified at the foundation, including unsystematic waste management, limited cleanliness awareness among some beneficiaries, and the absence of a structured, sustainable cleanliness program. The program combined interactive instruction and field practice, with evaluation conducted through pre- and post-tests using a 10-item multiple-choice questionnaire, participation observation, and a structured reflection session after the activity. Participants consisted of 20 children and adolescents under the foundation’s care. Activities included education, Q&A, and joint cleaning actions in the foundation environment. Findings indicate improved participant understanding and awareness based on comparisons between pre- and post-test results, with the most notable gains in cleanliness awareness and active engagement in waste handling and shared-facility maintenance. Overall, service-learning contributed positively by strengthening participation and fostering social responsibility for maintaining a clean and healthy environment within the foundation.